Mulheres trabalhadoras em movimento: MMT e MMB na Paraíba nos anos de 1980 - Souza, Laianny Cordeiro Silva de (2019)
In this dissertation, I deal with a representation on the trajectory of the Movimento de Mulheres Trabalhadoras – MMT and the Movimento de Mulheres Trabalhadoras do Brejo – MMB, throughout the 1980s. These groups worked in Paraíba, more precisely, in the mesoregions of Agreste and Mata Paraibana, in favor of rights and freedom of expression for women. In tracing these trajectories, I use in a qualitative way the narratives of eight women linked to these movements, as well, as the writings that contributed to my grounding in relation to the theme. Given the interviews, the present dissertation was previously authorized by the Ethics Committee of the Centro de Ciências da Saúde da Universidade Federal da Paraíba (Health Sciences Center of the Federal University of Paraíba). I signal that the work receives, mainly, the contributions of Cultural History and Oral History methodology. Thus, in the first chapter, I bring a brief explanation of the experiences lived in a singular way that marked the lives of the women interviewed; also, I describe the moment of my approach with these narrators invited to participate in this work. In the second chapter, I talk about the first interpretations about the narratives presented which begin to sketch how the groups were constituted and began to act. In this sense, I turn to the support and direction given by the work of the Catholic Church and the workers' unions that have undergone a process of renewal and have placed themselves alongside the workers, having made possible the space and the necessary awareness for the formation of groups. Also, discussing the changes, I continue the discussion with nuances that have taken place in the field of history and made possible the narratives like those of MMT and MMB to be researched and recorded in writing. I conclude the second chapter explaining the work of training the groups, considering the work of the coordination and the collaboration of the several women and entities that have supported the MMT and MMB. In the third and last chapter, I record the main collective activities, their impact on women's lives and what were the basic motivations and obstacles (among them, the conditions placed by the family in both movements, and by the Military Dictatorship, in the case of MMT ) that justified the existence of women's groups.